Methodical guidelines to perform calculation task in the discipline "Microeconomics" - Klimova, Svitlana; Volosnikova, Nataliia; Yatsyna, Viktoriia (National technical university "Kharkiv polytechnical institute", 2024)
Execution of calculation task on the subject "Microeconomics" is one of the components of the educational process and is an important element in the study of the discipline. This is one of the types of individual research tasks, that aims not only to deepen, generalize and consolidate students' knowledge of the discipline "Microeconomics", but also to apply them in solving a specific problem of modeling the behavior of market actors in a market economy, getting an ability to work independently with educational and scientific literature.
Keywords: methodical guidelines; analysis of supply; market equilibrium; economic activity; finance; competitiveness